Pravne obveznosti RS pri vključevanju otrok s posebnimi potrebami, zlasti otrok z motnjo v duševnem razvoju, v redne šole - Šelih, Alenka (Sodobna pedagogika, 2013)
The article starts by presenting the international legal documents that bind their signatory states to transpose the obligations imposed therein into their national legislation. Inclusive schools for children with special needs (SN) are provided for both by the United Nations Convention on the Rights of the Child, and the Convention on the Rights of Persons with Disabilities; Slovenia has ratified both conventions. The first one addresses effective access to education, while the second addresses the rights of disabled people to access education within an inclusive educational system. The article continues by outlining the non-binding international legal documents that specify these rights in reference to the various groups of children with SN, particularly children with mental development disorders (MDD). Having discussed the basic provisions related to integrating children with SN (especially those with MDD), the author concludes that in spite of the legal provisions enabling the integration of children with MDD into regular schools, this almost never happens in practice. She then lists some of the circumstances that have influenced the fact that even ten years after the legislation was adopted, its legal options have still not been implemented.
Keywords: otroci s posebnimi potrebami; duševne motnje; inkluzija; vzgoja in izobraževanje; človekove pravice; human rights